PENGARUH RISIKO KREDIT, RISIKO LIKUIDITAS DAN RISIKO OPERASIONAL TERHADAP KINERJA KEUANGAN - Widya Fadriyaturrohmah; Gusgana Suria Manda (FKIP, Universitas Banten Jaya, 2022)
This study was conducted to determine and analyze the financial performance of banking companies listed in the LQ 45 index for the 2014-2020 period. The factors analyzed are credit risk, liquidity risk and operational risk. The method used is descriptive. The data comes from the financial statements of banking companies incorporated in the LQ 45 index for the 2014-2020 period, namely Bank Central Asia (BCA), Bank Negara Indonesia (BNI), Bank Rakyat Indonesia (BRI), Bank Tabungan Negara (BTN) and Bank Mandiri. Data processing software using SPSS. This study partially obtains the results of credit risk and liquidity risk not having a significant effect on financial performance while operational risk has a significant effect on financial performance. So that credit risk, liquidity risk and operational risk simultaneously have a significant effect on financial performance.